An Islamic Spiritual Alternative to Addiction Treatment and Recovery - Benaouda Bensaid; Salah ben Tahar Machouche; Mustafa Tekke (Al-Jami'ah: Journal of Islamic Studies, 2021)
The Islamic spirituality permeating the practice of Muslim religious beliefs, values, and norms, is positioned to play a pivotal role in addiction prevention, treatment, rehabilitation therapy and recovery of Muslim addicts. This study seeks to explore potential interconnections between spirituality, addiction treatments, recovery, and the ways and means with which Islamic spirituality may assist addicts in coping with inner urges, relapse, and recovery. This study seeks to lay the groundwork for future theoretical and empirical research on spirituality and addiction, development of spirituality-based addiction programs, and the assessment of related current spiritual philosophies, methods, and strategies. This inquiry discusses spirituality as a source of meaning-making and purpose cultivation, self-discipline, motivation, support, reintegration, and related issues arising in these regards, and highlights the need for utilizing spirituality as a critical instrument in addiction treatment programs. Islamic spirituality however is neither – and should not be considered - a sole treatment scheme, nor does it appreciate absolute reliance on non-spiritual means of recovery in favor of positivistic empirical methods. [Spiritualitas Islam meresap ke pelbagai praktik keberagamaan, nilai dan norma, yang mana hal ini juga berperan penting pada pencegahan, pengobatan, terapi rehabilitasi dan pemulihan kecanduan pada umat muslim. Artikel ini mengeksplorasi potensi keterkaitan antara spiritualitas, penyembuhan kecanduan, pemulihan dan cara serta sarana spiritualitas Islam dalam membantu pecandu mengelola kondisi batin, ketika kambuh dan pemulihan. Studi ini berusaha meletakkan dasar bagi penelitian teoretis dan empiris dimasa depan tentang spiritualitas dan kecanduan, pengembangan program kecanduan berbasis spiritualitas, dan penilaian filosofi, metode, dan strategi spiritual terkait. Artikel ini membahas spiritualitas sebagai sumber pembentukan makna dan penggalian tujuan, disiplin diri, motivasi, dukungan, reintegrasi, dan isu-isu terkait yang timbul dalam hal ini, dan menyoroti kebutuhan untuk memanfaatkan spiritualitas sebagai instrumen penting dalam program perawatan kecanduan. Spiritualitas Islam bagaimanapun juga bukan–dan tidak boleh dianggap–satu-satunya skema pengobatan, tapi juga tidak tergantung mutlak pada sarana pemulihan non-spiritual yang mendukung metode empiris positivistik.]